Prophetic Leadership dalam Pengembangan Budaya Religius di Pondok Modern Arrisalah Gundik Slahung Ponorogo - Umar Sidiq; Qurrotul 'Uyun (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
This study is to describe and analyze 1) the strategy of prophetic leadership in the development of religious culture at Pondok Modern Arrisalah Gundik Slahung Ponororgo. 2) Supporting and inhibiting factors in the implementation of prophetic leadership at Pondok Modern Gundik Slahung Ponorogo. 3) The results of the application of prophetic leadership in the development of religious culture at Pondok Modern Arrislah Gundik Slahung Ponorogo. The concept of prophetic leadership that can be reached by the leadership of Pondok Modern Arrisalah is simply by imitating the Prophet Muhammad. according to human capacity. Generally, prophetic leadership is carried out by imitating the empathy of the Prophet's character. He is honest in everything, including adding knowledge honestly, really can be tested for sources. He is trustworthy to his leadership, does what he orders for all ustadz and his students, he also never disobeys his leadership. He is tabligh, conveying everything that he can so far for the benefit of the ustadz and his students. he is intelligent in all aspects of behavior and thought, so that so far he is the idol of the santri.